Penyimpanan dan Penataan Sarana dan Prasarana di SMPN Nuris Jember - Rofiq Hidayat; Nadia Mahsa Kalila; Ninin Anggraeni; Nur Fidayatullah; Oktavia Setia Ningrum (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the storage and arrangement system of facilities and infrastructure implemented at SMPN Nuris as an effort to improve the effectiveness of the learning process and the efficiency of school management. Well-managed facilities and infrastructure can create a safe, comfortable learning environment that supports the achievement of educational goals. The research method used is a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The findings show that although SMPN Nuris has a relatively structured system of storage and organization, there are still several challenges such as limited storage space, lack of regular maintenance, and minimal use of technology in inventory management. This study offers recommendations for improving the management system of facilities and infrastructure to support better school governance.